Gjb3 Gene Mutations in Non-Syndromic Hearing Loss of Bloch, Kurd, and Turkmen Ethnicities in Iran - Farnoush ALIAZAMI; Dariush D. FARHUD; Marjan ZARIF-YEGANEH; Siamak SALEHI; Azam HOSSEINIPOUR; Roxana SASANFAR; Maryam Eslami (Tehran University of Medical Sciences, 2020)
Background: Hearing loss (HL) is one of the most common heterogeneous congenital disabilities worldwide. Gap junction protein β-3 (GJB3) gene encodes Connexin31 protein (Cx31). The hereditary type of hearing impairment in this gene are known to cause both autosomal recessive and autosomal dominant form. In addition, GJB3 mutations have been involved in sensorineural deafness, erythrokeratodermia variabilis (EKV), and neuropathy diseases. We aimed to investigate GJB3 mutations in people suffering from HL among three different ethnicities of Iranian population (Baloch, Kurd, and Turkmen). Methods: In this descriptive study, 50 GJB2-negative non-syndromic hearing loss (NSHL) Iranian individuals from 3 ethnic groups of Baloch (n=17), Kurd (n =15) and Turkmen (n=18) were enrolled.  DNA extractions, PCR, and mutation detection was carried out for the two large deletions of the GJB6, del (GJB6 -D13S1830,) and del (GJB6 -D13S1854) followed by direct DNA sequencing method for the GJB3. Results: DNA sequencing of GJB3 was shown a missense heterozygous mutation rs199689484 (NM_024009.3) GJB3: c.340G>A (p.Ala114Thr) in a Baloch patient, and a polymorphism rs35983826 (NM_024009.3) GJB3: c.798C>T (p.Asn266=) in a Turkman patient, in coding region of the GJB3. We did not detect del (GJB6 -D13S1830) and del (GJB6 -D13S1854) among these three ethnicities in Iran. Conclusion: Deafness is a heterogeneous disorder. Specific genes and mutations contribute to hearing loss that varies from locus to locus as well as from population to population.